Correlation of delta high-resolution computed tomography (HRCT) score with delta clinical variables in early systemic sclerosis (SSc) patients - Suparaporn Wangkaew (2018)
© 2016 Quantitative Imaging in Medicine and Surgery. All rights reserved. Background: The correlation of changes (delta: Δ) of high-resolution computed tomography (HRCT) score with the Δ of other clinical variables has not been well studied. The purpose of this study was to determine the correlation of Δ HRCT score with Δ percent predicted forced vital capacity (%pFVC), Δ modified Rodnan Skin Score (mRSS), Δ erythrocyte sedimentation rate (ESR), and Δ percent of oxygen saturation at room air (%SpO2) in patients with early systemic sclerosis (SSc). Methods: We used an inception cohort of early-SSc patients seen at the Rheumatology Clinic, Chiang Mai University, Thailand, between January 2010 and June 2014. All patients underwent HRCT at study entry and every 12 months thereafter. Thirty-one SSc patients who underwent pulmonary function test (PFT) within 12 weeks of their corresponding HRCT at baseline and last visit were identified. The extent of ground glass (GG), lung fibrosis (Fib), bronchiectasis (B), and honeycombing (HC) was scored, and then aggregated to produce a total (t) HRCT score. Results: Mean ± SD age and disease duration from non-Raynaud's phenomenon (NRP) to undergo HRCT at baseline were 52.2±8.8 years and 11.7±7.1 months, respectively. Seventeen (54.8%) patients were female and 20 (64.5%) were classified as dcSSc. The mean ± SD interval between the two HRCT tests was 16.0±7.2 months. The Δ HRCT scores [total fibrosis scores (t-Fib), total bronchiectasis scores (t-B), and total HRCT score (t-HRCT) scores] and Δ mRSS, but not Δ %pFVC, showed significant change over the observation period. We found significant correlation of Δ total honeycombing scores (t-HC) with Δ ESR (r=-0.44, P<0.05), and Δ t-Fib with Δ %SpO2(r=-0.38, P<0.05). However, no significant correlation of any Δ HRCT scores with Δ %pFVC and Δ mRSS were observed. Conclusions: In this study, the changes in the HRCT scores were greater than %pFVC; this, along with their correlations with the changes in ESR and %SpO2, suggest that HRCT scores are a useful and sensitive method for monitoring disease progression in early SSc-related ILD (SSc-ILD).